Biografi dan Pemikiran Taqiyuddin An-Nabhani serta Pengaruhnya terhadap Pemikiran Ekonomi Islam - Rezaldi Supiandi; Ahmad Riandi; M.Amin al badari (LPPM Universitas Islam Indragiri, 2026)
This study is motivated by the dominance of conventional economic paradigms that view humans as homo economicus, primarily driven by self-interest and material gain, thereby neglecting moral and spiritual dimensions in economic activities. This research aims to analyze economic behavior from an Islamic perspective based on the thought of Taqiyuddin An-Nabhani and to examine its influence on contemporary Islamic economic thought. The study employs a qualitative approach using library research, utilizing secondary data from books and academic journals, with data collection through documentation and descriptive-analytical analysis. The findings indicate that economic behavior in Islam is not solely based on rationality but is influenced by aqidah, which shapes human mindset and behavior. Moreover, Islam clearly distinguishes between needs and wants and regulates ownership into three categories: private, public, and state ownership. An-Nabhani’s thought also contributes to the development of modern Islamic economics, particularly in wealth distribution and the role of the state. The study concludes that economic behavior in Islam integrates both material and spiritual aspects and remains relevant as an alternative framework for addressing contemporary economic issues.